Implikasi Putusan MK Nomor 18/PUU-XVII/2019 terhadap Asas Parate Eksekusi dalam Jaminan Fidusia - Maddhawati, Meitta; Siti Malikhatun Badriyah (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study analyzes the implications of Constitutional Court Decision Number 18/PUU-XVII/2019 on the application of the parate execution principle in fiduciary security. The research is motivated by the transformation of fiduciary execution, where parate execution can no longer be exercised unilaterally by creditors without debtor consent regarding default or a court decision. This study employs a normative juridical research method using statutory, conceptual, and case approaches to examine changes in the legal meaning and implementation of parate execution after the Constitutional Court’s decision. The findings indicate that the decision does not abolish parate execution but conditions its application on specific procedural requirements, including debtor acknowledgment of default and judicial oversight in the event of disputes. Accordingly, the scope of creditors’ direct execution rights becomes limited, while legal protection for debtors is strengthened through the application of the due process of law principle. The study concludes that the Constitutional Court Decision represents a recalibration of the parate execution principle within fiduciary law rather than its complete elimination.